2019
DOI: 10.1016/j.bbrep.2019.100642
|View full text |Cite
|
Sign up to set email alerts
|

CD44 aptamer mediated cargo delivery to lysosomes of retinal pigment epithelial cells to prevent age-related macular degeneration

Abstract: Age related macular degeneration (AMD) is a progressive, neurodegenerative disorder that leads to the severe loss of central vision in elderlies. The health of retinal pigment epithelial (RPE) cells is critical for the onset of AMD. Chronic oxidative stress along with loss of lysosomal activity is a major cause for RPE cell death during AMD. Hence, development of a molecule for targeted lysosomal delivery of therapeutic protein/drugs in RPE cells is important to prevent RPE cell death during AMD. Using human R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 27 publications
(32 reference statements)
0
12
0
Order By: Relevance
“… 53 Increasing evidence has suggested that CD44 play a significant role in the development of various inflammatory diseases and is over expressed in disease conditions. 53 , 54 It has been reported that CD44 receptors affinity for HA enables cells to internalize large HA-coated molecules. This receptor mediated uptake allows negatively charged NPs to still be taken up efficiently by retinal cells.…”
Section: Resultsmentioning
confidence: 99%
“… 53 Increasing evidence has suggested that CD44 play a significant role in the development of various inflammatory diseases and is over expressed in disease conditions. 53 , 54 It has been reported that CD44 receptors affinity for HA enables cells to internalize large HA-coated molecules. This receptor mediated uptake allows negatively charged NPs to still be taken up efficiently by retinal cells.…”
Section: Resultsmentioning
confidence: 99%
“…The first is a DNA aptamer with mono-thiophosphate modification targeting the HABD region of CD44 and was identified using in vitro SELEX using E. coli synthetic recombinant protein of the HABD [22]. It was demonstrated to bind several ovarian cancer cell lines [22] and an age-related macular degeneration model [23] with a binding affinity with KD of 181nM . A recent study showed that this CD44 aptamer alone could reduce SNAIL expression and migratory property of a breast cancer cell line [24].…”
Section: Discussionmentioning
confidence: 99%
“…Few example, transferrin-receptor-specific monoclonal antibody on the surface of transgene-containing liposomes, when introduced into retina-specific drug delivery for CNV treatment, showed expression of transgenes throughout the RPE and multiple areas of ocular tissues [ 124 ]. Another study in which an RPE-specific drug delivery platform was used in AMD and vitreoretinopathy as a conjugate (in vitro) observed that CD44-specific RNA aptamer-FITC conjugates were efficiently taken up by the RPE-overexpressing CD44 receptors via a receptor-mediated endocytosis pathway [ 125 ].…”
Section: Conjugation Approachesmentioning
confidence: 99%